Local T-spline surface skinning with shape preservation. (November 2018) - Oh, Min-Jae; Roh, Myung-Il; Kim, Tae-wan
Abstract: Surface skinning is a surface generation method that uses a set of given cross-sectional curves, and it is widely used in free-form surface design. In the B-spline surface skinning, the given B-spline curves should be compatible, that is, the curves should have the same degree and knot sequence. While making the curves compatible, lots of control vertices are generated. Although T-spline surface skinning methods have been introduced to reduce the number of control vertices, the T-spline skinning method that was proposed by Nasri et al. (2012) can generate a wiggled surface when the given B-spline curves are not sufficiently compatible. The intermediate cross sections that were introduced for T-spline surface skinning cannot preserve the shape of the given B-spline curves if the adjacent B-spline curves do not have sufficient common knots, and it can cause wiggles on the surface. In this paper, we analyze this issue and suggest a modified method to remove the wiggles on the skinned T-spline surface. Furthermore, we propose an algorithm for shape preservation of the surface. Our approach is verified by suggesting some examples compared to the Nasri et al. (2012)'s method. Graphical abstract: Highlights: A local T-spline surface skinning method with shape preservation is proposed. Refining the given cross sections is not necessary to remove wiggled shape on the skinned surface. Compatibility of given cross sections is not necessary. Shape control of the final T-spline surface is more flexible.